Simulating Soil Organic Carbon in a Wheat–Fallow System Using the Daycent Model. (1st November 2016) - Bista, Prakriti; Machado, Stephen; Ghimire, Rajan; Del Grosso, Stephen J.; Reyes‐Fox, Melissa
Abstract : Crop management practices that contribute to soil organic carbon (SOC) sequestration can improve productivity and long‐term sustainability. A simulation study was conducted using the DAYCENT model over an 80‐yr period. The objectives of the study were to assess model performance and forecast SOC changes in conventional tillage and no‐tillage management in a dryland winter wheat ( Triticum aestivum L.)–summer fallow (WW–SF) system. The treatments studied included fall burning of crop residue (FB0), no burning of crop residue with 0 (NB0), 45 (NB45) and 90 (NB90) kg N ha −1, pea vines (PV), and cattle manure (MN) addition. The model was accurate with R 2 values of 0.93 ( p < 0.01), 0.95 ( p < 0.01), and 0.99 ( p < 0.01) for the mean of observed and modeled grain yield, residue yield, and SOC, respectively. The strong positive correlation ( r = 0.71–0.91) in different treatments between observed and modeled SOC indicated that model closely simulated the observed values. DAYCENT projected that conventionally tilled WW–SF systems, except MN, lost 866 to 2192 g C m −2 SOC from 1931 to 2080. The MN gained 496 g C m −2 SOC in the same period. The conversion to no‐tillage from 2011 onward, however, minimized SOC loss by 17 to 47% under different WW–SF systems. No‐tillage conversion in MN resulted in SOC gain by more than 300%. This study suggested that adoption of a no‐tillage system and the addition of organic amendments can improve the long‐term sustainability of dryland WW–SF systems. Management practices that contribute to soil organic C sequestration can improve productivity. DAYCENT model simulated the influence of crop residue and nutrient management on soil organic C. Conventionally tilled winter wheat–summer fallow systems, except manure, lost soil organic C from 1931 to 2080. Conversion to no‐tillage had positive effects on soil organic C accumulation in winter wheat–summer fallow systems.